The Pain of Invisibility: A Perspective on the Treatment of Pediatric Chronic Pain - Kao, Grace S (J Patient Exp, 2020)
Although chronic pain can be debilitating and severely impacting, it can also be an affliction many take on privately. For many chronic pain patients and their families, the toll of symptom invisibility is often a prominent concern. The article expounds upon the theme of “symptom invisibility” and the need for and practice of developing a validating provider–family relationship in the treatment of children and adolescents with chronic pain. Suggestions for therapeutic pathways to building adaptive validation are provided.